2016
DOI: 10.1111/1440-1681.12649
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in vascular endothelial cells

Abstract: SummaryThe importance of autophagy in cardiovascular physiology and cardiovascular disease is increasingly recognized; however, the precise biological effects and underlying mechanisms of autophagy in the cardiovascular system are still poorly understood. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 72 publications
(244 reference statements)
1
84
0
2
Order By: Relevance
“…Indeed, a careful analysis of existing RTC and related meta-analysis studies on the effects of vitamin D supplementation reveals several methodological limitations, including the use of diverse study populations, different doses of vitamin D with or without Ca 2+ , different durations of supplementation and follow-up, different baseline and acquired circulating 25(OH)D concentrations, and different study outcome parameters [99,201]. Furthermore, significant discrepancies could result from the large inter-individual variation in genetic determinants of the efficacy of vitamin D supplementation [12,109,110], as well as its context-dependent effects on mechanisms in endothelial cells, including autophagy [202]. Consistent with these potential shortcomings in evaluating the effects of vitamin D supplementation, there remains much controversy and an open debate about the reliability of either RCTs or their meta-analyses [99,203,204].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a careful analysis of existing RTC and related meta-analysis studies on the effects of vitamin D supplementation reveals several methodological limitations, including the use of diverse study populations, different doses of vitamin D with or without Ca 2+ , different durations of supplementation and follow-up, different baseline and acquired circulating 25(OH)D concentrations, and different study outcome parameters [99,201]. Furthermore, significant discrepancies could result from the large inter-individual variation in genetic determinants of the efficacy of vitamin D supplementation [12,109,110], as well as its context-dependent effects on mechanisms in endothelial cells, including autophagy [202]. Consistent with these potential shortcomings in evaluating the effects of vitamin D supplementation, there remains much controversy and an open debate about the reliability of either RCTs or their meta-analyses [99,203,204].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current prediction analysis and luciferase activity determination, ATG16L1 is a target gene of let-7d, and let-7d can negatively regulate ATG16L1. It has previously been reported that various biological factors and chemical compounds are engaged in autophagy in vascular endothelial cells (VEcs), and autophagy has potential effects on endothelial cells (34). There is evidence showing the involvement of miRNAs in autophagy through the regulation of ATGs or their regulators in human diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is widely involved in physiological and pathological activities of endothelial cells. 11 It is worth noting that it can be induced by mechanical and biochemical factors, including shear stress, calcium and oxidative stress, [15][16][17] which are also influenced by decompression-induced intravascular bubbles. [18][19][20][21][22] We speculated that autophagy was probably involved in bubble-induced endothelial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, a cellular lysosome‐dependent degradation process, widely participates in physiological and pathological activities of endothelial cells such as proliferation, migration and angiogenesis . The role of autophagy involved in endothelial injury in atherosclerosis, ischaemia‐reperfusion, hepatopulmonary syndrome and other diseases has been well studied .…”
Section: Introductionmentioning
confidence: 99%